Isolation, structure, and functional elucidation of a modified pentapeptide, cysteine protease inhibitor (CPI-2081) from streptomyces species 2081 that exhibit inhibitory effect on cancer cell migration - Singh, Jay Prakash; Tamang, Sudarsan; Rajamohanan, P. R.; Jima, N. C.; Chakraborty, Goutam; Kundu, Gopal C.; Gaikwad, Sushama M.; Khan, Mohammad Islam (Journal of Medicinal Chemistry, 2010)
Cysteine proteases play an important role in cell migration and tumor metastasis. Therefore, their inhibitors are of colossal interest, having potential to be developed as effective antimetastatic drugs for tumor chemotherapy. Traditionally, secondary metabolites from streptomyces show a wide range of diversity with respect to their biological activity and chemical nature. In this article, we have described the characterization of small molecule cysteine protease inhibitor, CPI-2081 (compound 1), a mixture of two novel pentapeptides, compound 1a (736.71 Da), and compound 1b (842.78 Da), isolated from Streptomyces species NCIM2081, following solvent extraction and repeated HPLC based on C18 chemistry, and completely characterized using a variety of both ID and 2D NMR spectroscopy. Further, it was found that nanomolar concentration of compound 1 is able to inhibit papain hydrolytic activity. Also, compound 1 significantly inhibits tumor cell migration at sub cytotoxic concentration, indicating its remarkable potential to be developed as antimetastatic drug, which will make chemotherapy more localized and specific, thereby minimizing the hazardous side effects on normal tissues.

In vitro enzyme mediated synthesis of metal sulfide nanoparticles: control of particle size of CdS, Ni7S6, PbS, Co3S4 nanoparticles using synthetic peptides - Ansary, Abu Ayoobul; Khan, Muhammed I.; Gaikwad, Sushama M. (Science of Advanced Materials, 2012)
We report the use of enzyme sulfite reductase for the in vitro synthesis of technologically important metal sulfide quantum dots viz. Co3S4, PbS and Ni7S6. Also we report the use of synthetic peptides to control the particle size of the above metal sulfide quantum dots in addition to CdS, synthesized using enzyme. Sulfite reductase when incubated with aqueous CdCl2, or Co(NO3)(3) or NiCl2 or Pb(NO3)(2), and Na2SO3 in the presence of the appropriate capping peptide resulted in the synthesis of particle size controlled CdS, Co3S4, Ni7S6, or PbS quantum dots respectively. These, enzyme mediated synthesized and size controlled metal sulfide quantum dots, were characterized using Absorbance and photoluminescence spectrometry, X-ray diffraction, X-ray photoelectron spectroscopy and High resolution-transmission electron microscopy.
Keywords: Capping Peptide; Enzyme; Metal Sulfide Nanoparticles; quantum dots; Size Control; Sulfite Reductase

Insect trehalase: physiological significance and potential applications - Shukla, Ekta; Thorat, Leena J.; Nath, Bimalendu B.; Gaikwad, Sushama M. (Glycobiology, 2015)
Trehalose, a non-reducing disaccharide, is widespread throughout the biological world. It is the major blood sugar in insects playing a crucial role as an instant source of energy and in dealing with abiotic stresses. The hydrolysis of trehalose is under the enzymatic control of trehalase. The enzyme trehalase is gaining interest in insect physiology as it regulates energy metabolism and glucose generation via trehalose catabolism. The two forms of insect trehalase namely, Tre-1 and Tre-2, are important in energy supply, growth, metamorphosis, stress recovery, chitin synthesis and insect flight. Insect trehalase has not been reviewed in depth and the information available is quite scattered. The present mini review discusses our recent understanding of the regulation, mechanism and biochemical characterization of insect trehalase with respect to its physiological role in vital life functions. We also highlight the molecular and biochemical properties of insect trehalase that makes it amenable to competitive inhibition by most glycosidase inhibitors. Due to its crucial role in carbon metabolism in insects, application of inhibitors against trehalose can form a promising area towards formulating strategies for insect pest control.
Keywords: carbohydrate metabolism; glycosidase inhibitor; glycoside hydrolase; trehalase; trehalose

Investigation of structural and saccharide binding transitions of Bauhinia purpurea and Wisteria floribunda lectins - Agrawal, Sanskruthi B.; Ghosh, Deepanjan; Gaikwad, Sushama M. (Archives of Biochemistry and Biophysics, 2019)
Two novel medicinally important legume lectins from Bauhinia purpurea (BPL) and Wisteria floribunda (WFL) possessing extended sugar binding site were investigated for functional and conformational transitions using biochemical and biophysical techniques as well as bioinformatical tools. Homology model of BPL was constructed using the Schrodinger suite and docked with N-acetyl galactosamine and T-antigen disaccharide (Gal beta 1-3GalNAc alpha O-Me). The longer loop D in the structure of WFL compared to that in BPL was found to be responsible for its specificity to LacdiNac (beta-D-GalNAc-[1 -> 4]-DGlcNAc) over Gal beta 1-3GalNAc. BPL remained functionally stable up to 40 degrees C whereas WFL remained stable upto 70 degrees C indicating the strength of the sugar binding site geometry. Both the lectins showed intense but non-specific secondary structure in the range of 65-90 degrees C. WFL showed rapid aggregation above 80 degrees C as indicated by light scattering intensity. The lectins showed simultaneous dissociation and multistate unfolding in the vicinity of GdnHCl. At pH 1.0, both the lectins exhibited molten globule like structures, which were characterized further and were found to respond in a different way towards denaturants. The results have provided valuable insights into the molecular basis of the activity and stability of the two lectins.
Keywords: Conformation; Homology model; Lectin; Molten globule; saccharide binding; Thermal aggregation